Intensity correction for multichannel hyperpolarized 13C imaging of the heart. Issue 2 (1st December 2015) - Dominguez‐Viqueira, William; Geraghty, Benjamin J.; Lau, Justin Y.C.; Robb, Fraser J.; Chen, Albert P.; Cunningham, Charles H.
Abstract : Purpose: Develop and test an analytic correction method to correct the signal intensity variation caused by the inhomogeneous reception profile of an eight‐channel phased array for hyperpolarized 13 C imaging. Theory and Methods: Fiducial markers visible in anatomical images were attached to the individual coils to provide three dimensional localization of the receive hardware with respect to the image frame of reference. The coil locations and dimensions were used to numerically model the reception profile using the Biot‐Savart Law. The accuracy of the coil sensitivity estimation was validated with images derived from a homogenous 13 C phantom. Numerical coil sensitivity estimates were used to perform intensity correction of in vivo hyperpolarized 13 C cardiac images in pigs. Results: In comparison to the conventional sum‐of‐squares reconstruction, improved signal uniformity was observed in the corrected images. Conclusion: The analytical intensity correction scheme was shown to improve the uniformity of multichannel image reconstruction in hyperpolarized [1‐ 13 C]pyruvate and 13 C‐bicarbonate cardiac MRI. The method is independent of the pulse sequence used for 13 C data acquisition, simple to implement and does not require additional scan time, making it an attractive technique for multichannel hyperpolarized 13 C MRI. Magn Reson Med 75:859–865, 2016. © 2015 Wiley Periodicals, Inc.